A hydraulic fiber Bragg grating force sensor and its monitoring system for axial bolt load measurement in anchorage engineering. (23rd October 2018) - Liang, Minfu; Fang, Xinqiu; Wu, Gang; Chen, Ningning; Ning, Yaosheng; Gu, Chao
Abstract: The bolt support is one of the most important types of active support in anchorage engineering. The anchorage quality of the bolt is directly linked to the safety and stability of the anchorage engineering. Therefore, it is very important and necessary to monitor the stress state of the bolt. Conventional monitoring instruments are susceptible to electromagnetic interference and can not implement remote long-term monitoring and quasi-distributed measurement. A hydraulic-type FBG sensor for axial bolt load measurement is presented, comprising a pressure ring as a load-carrying structure, hydraulic oil as a transfer medium, an elastic diaphragm and a cantilever as sensitizer, and a FBG as the sensing element. The overall structure and working principle of the sensor are introduced in detail, and the theoretical relationship between the FBG wavelength shift difference and the force is established. Accurate force measurement can be obtained by monitoring the two FBGs' wavelength shift difference. The experimental results show that the average force sensitivity is 39.61 pm kN −1 in the range of 0–100 kN, and the linear coefficient is above 99.88%. The measurement sensitivity is improved by using the wavelength shift difference as the monitoring data, which avoids the cross-sensitive influence. In addition, WDM and SDM technology is adopted for constructing a FBG quasi-distributed measurement system to realize on-line monitoring of axial bolt load. The sensor proposed in this paper has wide application prospects in the field of health monitoring in anchorage engineering.